History in the Public Domain - Aquil, Raziuddin, (Brill | Manohar Publishers & Distributors, 2023)
History is a hot topic in popular politics of the public domain. Pressures from different kinds of ideological positions and politics of identities of various kinds put serious constraints on the practice and writing of history. Despite the challenges, scholarship has continued to grow. Current historiographical thrusts illustrate how a whole range of themes and issues are dealt with by professional historians from a variety of perspectives with reference to sources and evidence. For instance, issues relating to the complex interactions between religion and political culture are no longer being swept under the carpet. This collection of short essays and extended discussions on current research aims to intervene in public debates on what exactly happened in history. Given the situation, attempts of this kind can possibly help in somewhat bridging the wide gap between serious academic research and misplaced assumptions of popular histories. Much as historians are accused of merely speaking to themselves (and boring others), they need to be taken seriously when intervening in public debates using specialized historical methods and practices. Historical research conducted in universities can inform popular debates in newspapers, television channels, social media, and roadside dhabas for that matter, to lift the discussion to an informed intellectual plank and to bring about historical literacy and civility in the public domain.